Pengaruh Konflik Peran, Ketidakjelasan Peran, Kelebihan Peran, dan Gaya Kepemimpinan terhadap Kinerja Auditor Di Kantor Akuntan Publik Wilayah DKI Jakarta - Hendra Gunawan; Zulfitry Ramdan (Bina Nusantara University, 2012)
The purpose of this research is to determine and obtain empirical evidence on the factors related to the behavior of auditors that could affect the performance of auditors who work in Public Accounting Firm (KAP) Jakarta. This research discusses the factors regarding role conflict, role ambiguity, role excess, and leadership style. The writer took samples using convenience sampling technique. Criterion sampling was auditor working on the Firm in Jakarta with minimal education S1 majoring in Accounting with a minimum of one year working experience. Writers obtained research data through questionnaires distributed directly or via email to the auditors. The writers deployed 250 questionnaires to the auditors who worked on the Firm in Jakarta where questionnaires were successfully returned as many as 186 questionnaires, but there are 18 questionnaires that did not meet the criteria, so that 168 samples were used in this study. To obtain the results of the study, researchers used multiple regression analysis. The results of this study indicate that the independent variables included in this study, the lack of clarity of roles, have a significant influence on the performance of auditors. While, the other three independent variables: role conflict, role excess, and leadership style do not significantlyaffect the performance of the auditor.